HYPERTHYROIDISM IN ELDERLY PATIENTS AND HYPERTHYROID MYOPATHY: CASE REPORT AND LITERATURE REVIEW (Proceedings of the International Conference on Public Health, 2022)
Hyperthyroidism is the excessive production of thyroid hormone causingpalpitation, hypertension, weight loss, heat intolerance, tremor, anxiety, etc.Hyperthyroidism in elderly patients does not display typical features, making diagnosisdifficult. Hyperthyroid myopathy in elders is often mistaken for normal aging. It involvesmostly proximal muscles for unclear reasons. This case reports hyperthyroidism in anelderly patient. A 70-year-old female was presented with chest discomfort intermittentlyfor over 10 years and exacerbated for 10 days. This discomfort was described as chesttightness and palpitation. She also experienced shortness of breath. On physicalexamination, an enlarged thyroid was palpated. Thyroid ultrasound revealed diffusethyroid nodules. Thyroid function tests showed increased free and total triiodothyronine,free thyroxine, thyrotropin receptor antibodies, as well as a decreased thyroid-stimulatinghormone. Her clinical findings and lab tests were consistent with Graves’ disease, acondition of hyperthyroidism. Her condition was well managed with an antithyroid drugand beta-blocker. Hyperthyroidism in elderly patients may present only withcardiovascular disorders such as atrial fibrillation. In this case, the patient only displayedchest tightness and palpitation. Diagnosing hyperthyroidism in elders requires vigilanceand we should not dismiss any diagnostic hint. Through literature review, a potential linkbetween hyperthyroid myopathy and mitochondrial pathology is observed, which can befurther investigated using mitochondrial histochemistry and beta-blockade experiment.This study hopes to promote awareness of thyroid diseases in the elderly population andaddress the issue of myopathy in elders due to thyroid diseases.
Keywords: hyperthyroidism; senile hyperthyroidism; Graves' disease; hyperthyroid myopathy; mitochondrial myopathy; elderly patients